Peran pemerintah dan masyarakat dalam penyelenggaraan pendidikan: sistematik reviu - Titik Yuliana; Siti Maysaroh (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
This article examines issues related to the role of government and society in the context of education. The main focus of this research is to analyze how the government and society can contribute to advancing the education system, achieving effective educational goals, and improving the quality of education. The aims of this research are 1). Analyzing the government's role in the development and development of the national education system. 2) Identify the government's efforts to improve accessibility, equity, and quality of education. 3) Researching the role of the community in supporting and strengthening the national education system. The method used in this study is a literature review. The author conducted a search for relevant literature through academic sources such as scientific journals, books, research reports and government publications. The data found were then analyzed systematically and categorized based on themes and concepts related to the role of government and society in education. The results of this study indicate that the government has a responsibility to provide quality education, facilitate accessibility, develop relevant curricula, and improve teaching quality. Meanwhile, the community has an active role in supporting education through participation in educational decision making, financial support, and involvement in school activities. Based on the literature review in this study, it can be concluded that collaboration between government and society is very important. Close cooperation is required between the two parties to address various educational challenges. Future research can explore effective strategies and policies to involve the community in educational decision making.